Analysis of the Impact of Leadership, Organizational Culture, and Career Development on the Quality of Creative Industry Employees in Indonesia - Khuan, Hendri; Nugroho, Robertus Adi; Santi Diwyarthi, Ni Desak Made; Mas Wiartha, Nyoman Gede; Irdhayanti, Efa (West Science Interdisciplinary Studies, 2024)
This research investigates the impact of leadership styles, organizational culture, and career development on the quality of creative industry employees in Indonesia. Using a quantitative approach, a sample of 300 professionals from the creative sector was analyzed. The measurement model evaluation confirmed the reliability and validity of the constructs, while the structural model revealed significant positive relationships between leadership styles, organizational culture, and career development with the quality of creative industry employees. The results provide valuable insights for organizational strategies and practices within the Indonesian creative industry, emphasizing the importance of visionary leadership, innovative culture, and career development opportunities in enhancing the quality of creative outputs.